Toxic Effect of Cadmium on Rice as Affected by Nitrogen Fertilizer Form - Muhammad Jaffar Hassan; Feng Wang; Shaukat Ali; Guoping Zhang (Plant and Soil, 2005)

Selfing and inbreeding depression in seeds and seedlings of Neobalanocarpus heimii (Dipterocarpaceae) - Yoko Naito; Akihiro Konuma; Hiroyoshi Iwata; Yoshihisa Suyama; Kenji Seiwa; Toshinori Okuda; Soon Leong Lee; Norwati Muhammad; Yoshihiko Tsumura (Journal of Plant Research, 2005)

Water quality fluctuations under floating net cages for fish culture in Lake Cirata and its impact on fish survival - Irzal EFFENDIE; Kukuh NIRMALA; Umar HASAN SAPUTRA; Agus Oman SUDRAJAT; Muhammad ZAIRIN; Hisashi KUROKURA (Fisheries Science, 2005)

Comparative study on vegetative, reproductive and qualitative traits of seven diploid and tetraploid watermelon lines - Muhammad J. Jaskani; Sung W. Kwon; Dae H. Kim (Euphytica, 2005)

Measurements and Theory of Normal Tracheal Breath Sounds - Raphael Beck; Giora Rosenhouse; Muhammad Mahagnah; Raymond M. Chow; David W. Cugell; Noam Gavriely (Annals of Biomedical Engineering, 2005)

A simple procedure for simulating surge infiltration using first‐surge infiltrometer data - Sajid Mahmood; Muhammad Latif (Irrigation and Drainage, 2005)
The objective of this study was to modify a ring infiltrometer and to develop a simple and generic technique for simulating cumulative infiltration under constant on‐time surge cycles. A ring infiltrometer was modified by connecting a pipe arm for inward and outward water flow to the ring and from the ring to the pipe to create on–off surge cycles respectively. The Kostiakov infiltration equation was modified by introducing“surge factors” to simulate infiltration data for subsequent surges, using first surge infiltrometer data. The modified form of the Kostiakov equation is called the, “Azeemi–Kostiakov equation”. The unknown parameters of the Kostiakov equation were determined by applying the two‐point technique. Results of the study revealed that the infiltration data simulated by the Azeemi–Kostiakov equation matched closely with those collected from the surge‐ring infiltrometer. A significant reduction in the cumulative infiltration during different surges was also observed which varies from 61 to 84% for the first surge and from 30 to 61% for the subsequent surges. On an overall basis, the significant advantage of the Azeemi–Kostiakov equation is its application in simulating cumulative infiltration of subsequent surges by successfully using limited infiltrometer data. The validity of the Azeemi–Kostiakov equation outside the conditions of the experiments and for varying on–off surge cycles needs to be verified in order to extend its applicability. If this is done, the prior estimation of infiltration for a desired set of on–off surge cycles through this method would permit planning of surge irrigation studies for efficient water management. Copyright © 2005 John Wiley & Sons, Ltd.

Characterization of fusarium wilt-resistant and fusarium wilt-susceptible somaclones of banana cultivar rastali (Musa AAB) by random amplified polymorphic DNA and retrotransposon markers - Asif Javed Muhammad; Fofina Yasmin Othman (Plant Molecular Biology Reporter, 2005)

Relationship among acidophilic bacteria from diverse environments as determined by randomly amplified polymorphic DNA analysis (RAPD) - Tanveer Akbar; Kalsoom Akhtar; Muhammad A. Ghauri; Munir A. Anwar; Moazur Rehman; Mehboobur Rehman; Yusuf Zafar; Ahmad M. Khalid (World Journal of Microbiology and Biotechnology, 2005)

Molecular markers for yield components in Brassica juncea – do these assist in breeding for high seed yield? - Tariq Mahmood; Muhammad H. Rahman; Gary R. Stringam; Francis Yeh; Allen Good (Euphytica, 2005)

Bacterial Cr(VI) Reduction Concurrently Improves Sunflower (Helianthus Annuus L.) Growth - Muhammad Faisal; Shahida Hasnain (Biotechnology Letters, 2005)

Pathogenicity of bacterium, Xenorhabdus nematophila isolated from entomopathogenic nematode (Steinernema carpocapsae) and its secretion against Galleria mellonella larvae - Ali Nawaz Mahar; Muhammad Munir; Sami Elawad; Simon Richard Gowen; Nigel Graham Meckenzi Hague (Journal of Zhejiang University-SCIENCE B, 2005)

Chromate resistantBacillus cereus augments sunflower growth by reducing toxicity of Cr (VI) - Muhammad Faisal; Shahida Hasnain (Journal of Plant Biology, 2005)

Effect of seedling age and water depth on morphological and physiological aspects of transplanted rice under high temperature - Abdul Aziz Khakwani; Masaaki Shiraishi; Muhammad Zubair; Mohammad Safdar Baloch; Khalid Naveed; Inayatullah Awan (Journal of Zhejiang University-SCIENCE B, 2005)

Morpho-anatomical responses ofTrigonella foenum graecum Linn. to induced cadmium and lead stress - Syed Hilal Ahmad; Zafar Reshi; Javed Ahmad; Muhammad Iqbal (Journal of Plant Biology, 2005)

Comparison of cytotoxic activities betweenin vitro and field grown plants ofTyphonium flagelliforme (Lodd.) blume - Lai Keng Chan; Wan Yee Koh; Tengku S. Tengku-Muhammad (Journal of Plant Biology, 2005)

Greenhouse gas emissions from tropical peatlands of Kalimantan,Indonesia - Abdul Hadi; Kazuyuki Inubushi; Yuichiro Furukawa; Erry Purnomo; Muhammad Rasmadi; Haruo Tsuruta (Nutrient Cycling in Agroecosystems, 2005)

A Conceptual Framework for Enhancing the Utility of Rainfall Hazard Forecasts for Agriculture in Marginal Environments - Muhammad T. Usman; Emma Archer; Peter Johnston; Mark Tadross (Natural Hazards, 2005)

A facile and improved synthesis of sildenafil (Viagra) analogs through solid support microwave irradiation possessing tyrosinase inhibitory potential, their conformational analysis and molecular dynamics simulation studies - Khalid M. Khan; Ghulam M. Maharvi; Mahmud T. H. Khan; Shahnaz Perveen; Muhammad I. Choudhary; Atta-ur- Rahman (Molecular Diversity, 2005)

Exogenous IL-7 induces Fas-mediated human neuronal apoptosis: potential effects during human immunodeficiency virus type 1 infection - Giuseppe Nunnari; Yan Xu; Edward A Acheampong; Jianhua Fang; Rene Daniel; Chune Zhang; Hui Zhang; Muhammad Mukhtar; Roger J. Pomerantz (Journal of NeuroVirology, 2005)